Translations of Serhiy Zhadan’s Poetry in Intercultural Communication - Tetyana Shyliaieva (Journal of Danubian Studies and Research, 2023)
Our investigation looks into the role of poems of the Ukrainian writer Serhiy Zhadan translated into English and used in intercultural communication, as well as peculiarities of their translation. In the Danube region, where the echoes of war and displacement are felt, Zhadan’s poems find a profound connection between the struggles faced by local inhabitants and the experiences of those seeking refuge. The research objective of our work is study of inner mechanisms of translating poetry texts to reach lexico-grammatical, stylistic, and pragmatic adequacy of translation. The article analyzes imagery in Serhiy Zhadan’s three poems. The use of images of war and peace, our memories, home and other motifs is investigated. The research is based on the literary and translation analysis of the poems, as well as on the use of methods of stylistic analysis and literary criticism. The role of Serhiy Zhadan’s poems in promoting Ukrainian literature in international communication is highlighted.